Law Enforcement Against Fishing Ship Crews That Do Not Have A Sail Permit - Ismail Lasantu (Universitas Negeri Gorontalo, 2019)
Abstract: This study aims to determine and analyze Law Enforcement Against Crews of Fishing Vessels Who Do not Have Sailing Permits. The data used in this study were analyzed and presented descriptively by using a statute approach and case approach (case uproach) through a qualitative approach to secondary data and primary data. The results show that law enforcement against fishing vessel crews who do not have a sailing permit can basically be done by fixing and improving the system and management of licensing documents in a simple way with the one-stop integrated service method (PTSP) in improving the quality of service by presenting the harbormaster's representative office in every area/city district and conducting surveillance and patrols in areas frequented by ships to catch fish and the activity of the marine police in providing counseling to fishing communities with the aim of providing knowledge about the obligations of each ship captain or crew members to have a letter of approval to sail and take action based on the Criminal Procedure Code and other relevant laws and regulations as a formal source of law used in enforcing criminal law. a material through the imposition of imprisonment, payment of fines, warnings and coaching. Keywords: Law Enforcement, Crew, Permit to Sail r